On Curse and the Power of Knowledge: Upanishadic Moments and the Aṣṭāvakra Tale of the Mahābhārata - Shalom, Naama (Numen, 2025)
The Mahābhārata tells a horrid tale of curse; a father curses his son to be born eightfold deformed (aṣṭāvakra). This moment of curse occurs in the household of none other than Uddālaka Āruṇi, the great Upanishadic sage and his notorious son, Śvetaketu. Our article offers a reflection on the significance and meanings of the intertextual space – obviously not incidental – of the two traditions, the Mahābhārata epic and the Upaniṣads. The notion and conception of curse (śāpa) sheds light on the diagnosis of the human condition shared by the two traditions. It is a “cursed” condition of self-alienation and disease, which can be released by the power of “knowledge” (vidyā) and true health (svāsthya) that emanates from residing in oneself (ātman).